What Role Can Financial Policies Play in Revitalizing SMEs in Japan? - Lam, Waikei (IMF Working Papers; Working Paper, 2012)
The paper discusses the role the financial sector can play in supporting growth in Japan. While overall credit conditions have been accommodative, credit growth has remained weak, especially for small and medium-sized enterprises (SMEs). Firm-level SME data and sectoral corporate balance sheets show that many SMEs have faced structural challenges of high leverage and low profitability. Moreover, the global financial crisis has weakened the financial position across SMEs, particularly for those with low credit worthiness. These challenges are closely related to low availability of riskcapital and the pervasiveness of credit support measures. This paper argues that to encourage the supply of risk-based capital, costly government support measures should be phased out and SME restructuring be accelerated. Efforts are also needed to deepen capital markets to enhance risk capital availability and address regulatory barriers to starting businesses. In that regard, addressing SMEweaknesses would improve private investment, enhance firm productivity, and lift growth.